Fluid mechanics. - Kundu, Pijush K.; Cohen, Ira M.; Dowling, David R.; Capecelatro, Jesse (Academic Press, 2025)
Fluid mechanics, understanding and applying the principles of how motions and forces act upon fluids such as gases and liquids, is introduced and comprehensively covered in this text.